Efektivitas Media Pasir dalam Meningkatkan Kemampuan Membaca Permulaan bagi Anak Disleksia - Ulfa Alifia Ningrum; Arisul Mahdi (Jurnal Penelitian Pendidikan Khusus, 2023)
This study aims to prove that sand media is effective in improving early reading skills for dyslexic children. This study uses a type of experimental research with a single subject research A-B-A design. The research subject was a dyslexic child in grade III elementary school who still could not distinguish the letters b and d. Data collection techniques used reading tests, observations (observations) and interviews. The data collected is in the form of a score in the form of a percentage. Then, the data were analyzed by graphical visual analysis. Based on data analysis from three conditions for 16 meetings, the baseline condition (A1) shows stable data at 0% and flat (=). Baseline conditions (B) show unstable data of 33.33% and increase (+). The baseline condition (A2) shows 80% stable data and increases (+).The results of the research that has been carried out show that children's initial reading ability increases after being given an intervention using sand media. Thus, the sand media proved to be effective in improving beginner reading skills